A internet a serviço da evangelização - Ulprist, Adilson (2011)
Our era is marked by great technological development. The machine or rather, the computer has now become an integral part of human life. We can even take the liberty to say that it has become an extension of human hands. Involved with such technology, the man craves increasingly seek an answer to their existence and why in this world. This response will not find if he is not open to what we transcend. It is seeking an answer to this question that the Church is called to be present in the media to help man in this quest and make possible their relationship with the transcendent. The object of this study goes through the communication technology, and comes in the most modern of all the technologies of our time is the Internet. Seeking to show what is possible through a great communication tool like this to bring the Good News of Christ, but also thought and message of the Church for all who are connected. The proposal is that those involved in ecclesial universe do not look at the world wide web as extremely odd or liable to demonize them, but look at this great opportunity to use for the good of all